Impact of protein kinase CK2 downregulation and inhibition on oncomir clusters 17 ~ 92 and 106b ~ 25 in prostate, breast, and head and neck cancers - Betsy T. Kren; Christine M. Henzler; Khalil Ahmed; Janeen H. Trembley (BMC, 2024)
Abstract Background Protein kinase CK2 is a ubiquitous and highly conserved protein Ser/Thr kinase with diverse cell functions. CK2 is upregulated in various cancers and affects numerous aspects of their underlying pathobiology. The important role of microRNAs (miRNAs) referred to as oncomirs is also recognized in various cancers. Elevation of both CK2 and altered miRNA expression in cancers raised the question whether there was a connection between CK2 function and oncomirs in cancer. Methods PCR array analysis was used to examine the effects of CK2 siRNA-mediated downregulation on miRNA levels in C4-2 prostate cancer cells. We employed prostate cancer, breast cancer, and head and neck squamous cell carcinoma (HNSCC) cells as well as a prostate cancer xenograft orthotopic tumor model to examine the effects of CK2 siRNA-mediated downregulation or chemical inhibition on oncomir cluster miR-17 ~ 92 and miR-106b ~ 25 constituent miRNAs by quantitative reverse-transcriptase stem-loop PCR. Pri-miRNAs were measured in cancer cell lines by quantitative reverse-transcriptase PCR. Protein levels were assessed by western blot. PC3-LN4 prostate cancer orthotopic xenograft tumors and blood were collected from nude mice following repeated treatments with tenfibgen ligand nanocapsules containing RNAi-CK2 or RNAi-Control cargoes. Results PCR array analysis demonstrated effect on a subset of miRNAs following CK2 downregulation; we focused our investigation on CK2 regulation of miR-17 ~ 92 and 106b ~ 25 oncomir clusters. Chemical inhibition or molecular downregulation of CK2 greatly reduced expression of miR-17 ~ 92 and 106b ~ 25 in prostate, breast and head and neck cancer cells in vitro. CK2α and CK2α´ protein levels were significantly correlated with many of the miR-17 ~ 92 and some of the miR-106b ~ 25 constituent members in prostate cancer cells. Decreased pri-miRNA levels for the miR-17 ~ 92 gene cluster transcript were observed for 5 of 6 cancer cell lines tested following CK2 downregulation. Nanocapsule-mediated delivery of RNAi-CK2 reduced CK2 protein expression in orthotopic prostate xenograft tumors and decreased intra-tumoral and serum levels of the oncomirs. Conclusions Targeting CK2 for the development of new cancer therapies is under active investigation in many laboratories and pharmaceutical companies. Our data suggest a new role for CK2 in cell signaling and survival in multiple cancer types through maintenance of miR-17 ~ 92 and 106b ~ 25 biogenesis.